Keuu: el papel de la risa en la vida cotidiana de los waorani - Araque Contreras, Yeimy (2023)
This article presents keuu laughter as a fundamental element in the construction of the daily life of the Waorani people, located in the Ecuadorian Amazon. Keuu is a laughter that has the form of a scream, it is present in everyday forms of speech as well as in ancestral songs, and it is shared with the jaguar, the fundamental mythical being. This research was carried out by means of audiovisual ethnography. The video camera was part of the equipment used to observe an experience the Waorani sensitive reality. This article allows us to conclude that keuu is a performative, heartfelt and thought-out laughter, which when pronounced, it makes positive transformations in the world, contributing to the collective creation of acomfortable sociality. By laughing keuu the Waorani actualize mythical time, the experience of the ancestors and the kinship relationship with the jaguar as the founding father of their cosmology. Keuu reveals an aesthetics of life, in which laughter and humor are structuring elements of sociality